Klotho Inhibits Interleukin-8 Secretion from Cystic Fibrosis Airway Epithelia. Issue 1 (December 2017) - Krick, Stefanie; Baumlin, Nathalie; Aller, Sheyla Paredes; Aguiar, Carolina; Grabner, Alexander; Sailland, Juliette; Mendes, Eliana; Schmid, Andreas; Qi, Lixin; David, Nicolae; Geraghty, Patrick; King, Gwendalyn; et al.
Abstract Chronic inflammation is a hallmark of cystic fibrosis (CF) and associated with increased production of transforming growth factor (TGF) β and interleukin (IL)-8. α-klotho (KL), a transmembrane or soluble protein, functions as a co-receptor for Fibroblast Growth Factor (FGF) 23, a known pro-inflammatory, prognostic marker in chronic kidney disease. KL is downregulated in airways from COPD patients. We hypothesized that both KL and FGF23 signaling modulate TGF β-induced IL-8 secretion in CF bronchial epithelia. Thus, FGF23 and soluble KL levels were measured in plasma from 48 CF patients and in primary CF bronchial epithelial cells (CF-HBEC). CF patients showed increased FGF23 plasma levels, but KL levels were not different. In CF-HBEC, TGF-β increased KL secretion and upregulated FGF receptor (FGFR) 1. Despite increases in KL, TGF-β also increased IL-8 secretion via activation of FGFR1 and Smad 3 signaling. However, KL excess via overexpression or supplementation decreased IL-8 secretion by inhibiting Smad 3 phosphorylation. Here, we identify a novel signaling pathway contributing to IL-8 secretion in the CF bronchial epithelium with KL functioning as an endocrine and local anti-inflammatory mediator that antagonizes pro-inflammatory actions of FGF23 and TGF-β.